Potential Roles of the Free Salivary Microbiome Dysbiosis in Periodontal Diseases - Diao, Jing; Yuan, Chao; Tong, Peiyuan; Ma, Zhangke; Sun, Xiangyu; Zheng, Shuguo (Frontiers in Cellular and Infection Microbiology, 2021)
Saliva is a vital mediator in the oral cavity. The dysbiosis of free bacteria in saliva might be related to the onset, development, prognosis, and recurrence of periodontal diseases, but this potential relationship is still unclear. The objective of this study was to investigate the potential roles of the free salivary microbiome in different periodontal statuses, their reaction to nonsurgical periodontal therapy, and differences between diseased individuals after treatment and healthy persons. We recruited 15 healthy individuals, 15 individuals with gingivitis, and 15 individuals with stage I/II generalized periodontitis. A total of 90 unstimulated whole saliva samples were collected and sequenced using full-length bacterial 16S rRNA gene sequencing. We found that as the severity of disease increased, from healthy to gingivitis and periodontitis, the degree of dysbiosis also increased. A higher abundance of Prevotella intermedia and Catonella morbi and a lower abundance of Porphyromonas pasteri, Prevotella nanceiensis, and Haemophilus parainfluenzae might be biomarkers of periodontitis, with an area under curve (AUC) reaching 0.9733. When patients received supragingival scaling, there were more pathogens related to recolonization in the saliva of periodontitis patients than in healthy persons. Even after effective nonsurgical periodontal therapy, individuals with periodontitis displayed a more dysbiotic and pathogenic microbial community in their saliva than healthy individuals. Therefore, the gradual transition in the entire salivary microbial community from healthy to diseased includes a gradual shift to dysbiosis. Free salivary pathogens might play an important role in the recolonization of bacteria as well as the prognosis and recurrence of periodontal diseases.